Creative use of word and image in marketing strategies (on the example of real-time marketing) - Kacperska, Beata (Linguistic creativity in marketing, 2022)
The creators of marketing campaigns use various tools to effectively reach the awareness of potential consumers. The basic means in marketing communication are a word and an image and their effectiveness is often determined by an accurate and creative combination of both types of content — verbal and visual. This is evidenced by real-time marketing, a marketing strategy in which the image draw attention of the recipients and the text completes the entire presented message. The aim of the article is to show the ways of using current events and situations thematically related to Polish sport, including the significant successes of Polish representatives, to promote their own brand and build its positive image. The result of analyses of the collected empirical material is an indication of the constitutive features of verbal-visual messages created as part of real-time marketing: the complementarity of the meanings of a word and an image, the use of a spatial syntagma (most often in the top — bottom relationship), the use of reference and ambiguity.